2019
DOI: 10.1016/j.jtho.2018.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake Interacts with Functional Genetic Polymorphisms of Aldehyde Dehydrogenase (ALDH2) and Alcohol Dehydrogenase (ADH) to Increase Esophageal Squamous Cell Cancer Risk

Abstract: Introduction: Studies have reported alcohol consumption and genetic variants as major contributing factors for esophageal squamous cell carcinoma (ESCC). However, the complicated interactions between alcohol and genetic factors involved in alcohol metabolism have not been well elucidated with respect to augmented risk of ESCC. Alcohol Intake, ALDH2, ADH, and ESCC Risk 715 a Rs671 genotype AA is not included because of insufficient samples size.bProportion of drinkers in controls among different genotypes: of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…The research design and flow of subject recruitment have been described in detail previously ( 17–19 ). In brief, we performed a population-based, case-control study from 2010–2014 in Taixing, Jiangsu province, China, where the incidence of ESCC is high ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…The research design and flow of subject recruitment have been described in detail previously ( 17–19 ). In brief, we performed a population-based, case-control study from 2010–2014 in Taixing, Jiangsu province, China, where the incidence of ESCC is high ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Wu et al reported that consumption of alcohol only increased the risk of ESCC in males but not in females ( 36 ), as supported by another study that indicated that only males who drank alcohol had a 2.2-fold (95% CI: 1.79–2.70) higher ESCC risk ( 37 ). Mechanistically, a case-control study that enrolled 1,190 patients and 1,883 controls revealed that alcohol consumption could interact with aldehyde dehydrogenase and alcohol dehydrogenase (ADH), resulting in a markedly elevated ESCC incidence ( 38 ).…”
Section: Risk Factors Of Ecmentioning
confidence: 99%
“…Also the adverse role of loss-of-functional ADH and ALDH variants will increase in alcohol drinkers. Third, the mechanism of tumorigenesis may not be same with and without a family history of the esophageal cancer [52,53].…”
Section: Adhmentioning
confidence: 99%